Priorização de manutenção em uma empresa de saneamento: modelo multicritério híbrido de apoio a decisão - Andrade, Fernanda Gomes de (2020)
It is of vital importance to keeping the sanitation system working. Performing maintenance is a way of keeping the system running and ensuring that the service reaches the customers. But the task of integrating all the important aspects surrounding the maintenance prioritization decision is difficult and demands a method that assists in the decision-making process. To meet this demand, this paper aims to propose a hybrid multicriteria decision support model to prioritize corrective maintenance activities in a sanitation company. For this, an analysis of the decisionmaking process was carried out, the corrective maintenance prioritization criteria were defined, the SWARA method was used to determine the weights of the prioritization criteria from the decision-makers' opinion, and a multicriteria decision support model was proposed using fuzzy TOPSIS to prioritize alternatives. The results defined the use of seven criteria, showing customer service as the most important criteria. The model proved to be flexible and useful for solving the problem, meeting the needs of the company with the response of a reliable ranking that helps decision making.